2020
DOI: 10.3389/fnins.2020.00381
|View full text |Cite
|
Sign up to set email alerts
|

Combined Behavioral and Mismatch Negativity Evidence for the Effects of Long-Lasting High-Definition tDCS in Disorders of Consciousness: A Pilot Study

Abstract: Objective: To evaluate the effects of long-term High-definition transcranial direct current stimulation (HD-tDCS) over precuneus on the level of consciousness (LOC) and the relationship between Mismatch negativity (MMN) and the LOC over the therapy period in patients with Disorders of consciousness (DOCs).Methods: We employed a with-in group repeated measures design with an anode HD-tDCS protocol (2 mA, 20 min, the precuneus) on 11 (2 vegetative state and nine minimally conscious state) patients with DOCs. MMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…These studies have observed improvements both in the CRS-R scores and cortical functional connectivity of some patients. [ 84 86 ] Their preliminary results may provide insights into the basis for increasing the precision of therapeutic targets in relevant research; however, there is still little available information regarding the pathophysiological mechanisms of DOCs, there are numerous nuclei yet to be explored as potential targets. Therefore, at this stage, using conventional tDCS which stimulate a broader region is still the treatment of choice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have observed improvements both in the CRS-R scores and cortical functional connectivity of some patients. [ 84 86 ] Their preliminary results may provide insights into the basis for increasing the precision of therapeutic targets in relevant research; however, there is still little available information regarding the pathophysiological mechanisms of DOCs, there are numerous nuclei yet to be explored as potential targets. Therefore, at this stage, using conventional tDCS which stimulate a broader region is still the treatment of choice.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a non-invasive DBS approach, θ burst TMS pattern, and novel forms of transcranial electrical stimulation, such as HD-tDCS, tACS, and tRNS, have either been described or practiced in this field. [ 49 , 84 86 , 97 , 100 , 102 ] More innovations are worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Angelakis et al reported the effects of 2-week tDCS over left DLPFC in patients with different degrees of consciousness disorders, in which all the patients with MCS showed increased CRS-R scores at the end of the treatment (29). Another study demonstrated that 10 tDCS sessions over precuneus could improve the signs of consciousness in patients with DoC represented by CRS-R total scores (22). In addition, the auditory and motor CRS-R subscales scores were significantly higher post-2-week real tDCS than both the baseline and sham tDCS (Table 2), from which we speculated that the potential of tDCS may be related to its effect on auditory and motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…The CRS-R is a common scale for the assessment of consciousness, which was used to differentiate vegetative state (VS) from MCS and identify patients who have emerged from MCS (21). The CRS-R is comprised of six subscales, including auditory, visual, motor, oromotor, communication, and arousal function organized in 29 hierarchically items to reflect the level of consciousness and to track behavioral recovery, and each item has specific scoring criteria (22,23). In addition, adverse events related with the stimulation like allergies and redness of the skin were also recorded in the study.…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
“…Transcranial direct current stimulation [28][29][30][31][32][33][34][35][36]. DLPFC or posterior parietal cortex at 10-20 min/time (1-2 mA for 10-20 days) was chosen.…”
Section: Neurostimulation Therapymentioning
confidence: 99%